Evaluation of a High-Level Metamodel for Developing Smart Contracts on the Ethereum Virtual Machine - Velasco, Gislainy Crisostomo; Vieira, Marcos Alves; Carvalho, Sergio T. (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain); 2023: Anais do VI Workshop em Blockchain: Teoria, Tecnologias e AplicaçõesDO - 10.5753/wblockchain.2023.757, 2023)
Developers of smart contracts face challenges such as the immutability of contracts and asset storage, which make the activity complex and errorprone. To make contracts safer and more reliable, Model-Driven Engineering (MDE) offers an alternative approach with an emphasis on the High-Level Metamodel for Smart Contract (HLM-SC), which allows for the high-level declaration of elements within a contract. This paper evaluates the HLM-SC using the MQuaRE framework to verify its conceptual validity with 11 external evaluators. The results demonstrated the acceptance of the metamodel. Additionally, this paper presents a guide on how to use HLM-SC to facilitate its adoption by developers. Finally, it demonstrates the application of HLM-SC in a scenario related to the NFT industry.